La alimentación de algunas aves del orden Strigiformes en la Argentina - Massoia, Elio (1983)
Feeding habits of Argentinian owls; an analisis of cast pellets. The author studied the contents of 1421 cast pellets of the following Argentinian owls: Bam Owl, Tyto alba tuidara (3 samples of 1215, 116 and 58 pellets); Great Horned Owl Bubo virginianus nacurutu (2 samples of 14 and 18 pellets) and Burrowing Owl. Athene cuniculllria partridgei (10 pelleta). The results are presented in tables with the following information: place, date, prey species, numbers of individuals in each prey species, present of each prey species on total prey, and a two variable code representing main prey species (AP) and secondary prey species (AS). The principal conclusions of the prey marnmals studied are: Oligoryzomys is a valid genus. Bibimys sp. and Colomyslaucha ssp., coexisting in Misiones Province. The presence of Holochilus brasiliensu ssp. is verified in the Misiones Province. Oligoryzomys flavescens antonitae ssp. nov. is described. Bibimys torresi Massoia , 1978, is cited for first time in Entre Rios Province.